The Effect of the Level of Disclosure of Islamic Corporate Governance on Financial Performance at Indonesian Sharia Banks - Mediaty, Mediaty; Mustakim, Mustakim; Mas'ud, Anis Anshari; Muhammad, Gazali; Made, Sutinah (Perhimpunan Intelektual Muslim Indonesia, 2024)
The aim of this study was to analyze the effect of Islamic Corporate Governance Disclosure on financial performance in Indonesia. This disclosure encompasses various dimensions, including the board of directors, Sharia supervisory board, board committee, internal control, internal audit, and risk audit. The disclosure of Islamic Corporate Governance is crucial as it offers insights into how the financial performance of Islamic banks is managed, identifies the responsible managers, and outlines the steps taken in the management process. This research adopts an explanatory approach. The data utilized consists of secondary data spanning 2012 to 2020, gathered from 12 periodically selected Islamic commercial banks in Indonesia. The analysis method employed is content analysis, which derives disclosure values based on survey results. The results of this research contribute to the space and realm of knowledge development, particularly in relation to the advancement of theories or concepts regarding Islamic values in the implementation of Sharia banking activities.